PENGARUH MOTIVASI, PENGETAHUAN PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK (STUDI KASUS PADA WAJIB PAJAK ORANG PRIBADI DI WILAYAH KANTOR PELAYANAN PAJAK PRATAMA YOGYAKARTA) - Pratiwi, Anthonia Ditha Sendy; Sinaga, Klemensia Erna Christina (Universitas Multimedia Nusantara, 2023)
Abstract” This study aims to determine the effect of Motivation, Tax Knowledge, and Tax Sanctions on Tax Compliance in the Yogyakarta Primary Tax Service Office. The purpose of this research is motivated by the low compliance of individual taxpayers in fulfilling their obligations in the field of taxation. This research was conducted using a quantitative approach. The research data is in the form of primary data and data collection is carried out by distributing questionnaires to individual taxpayers in the Region of the Yogyakarta Primary Tax Service Office. The sampling technique used probability sampling with a sample size of 125 respondents. Data analysis technique using multiple linear regression analysis method. The conclusion of this study shows that Tax Motivation and Knowledge have an effect on Tax Compliance, while Tax Sanctions have no effect on Tax Compliance in the Region of the Yogyakarta Primary Tax Service Office. It is known from the Tax Motivation and Knowledge that it has a t count > t table with a significant value <0.05, which means that with an increase in Tax Motivation and Knowledge owned by each taxpayer, it will also increase tax compliance. Tax sanctions have a value of t count < t table with a significant value > 0.05 which indicates that administrative sanctions and criminal sanctions given to taxpayers do not cause a deterrent effect in tax compliance. Keywords: Motivation; Knowledge; Sanctions; Compliance; Taxes